A pirate's guide to recess - Ruth, Greg 1970- (Feiwel and Friends, 2013)
It's time for recess, and the schoolyard is teeming with young pirates ready for action
Keywords: Pirates / Juvenile fiction; School recess breaks / Juvenile fiction; Picture books for children; Pirates / Fiction; Schools / Fiction; Recess / Fiction; Pirates; School recess breaks